2012
DOI: 10.1088/0004-637x/754/1/29
|View full text |Cite
|
Sign up to set email alerts
|

H I Power Spectra and the Turbulent Interstellar Medium of Dwarf Irregular Galaxies

Abstract: H i spatial power spectra were determined for a sample of 24 nearby dwarf irregular galaxies selected from the Local Irregulars That Trace Luminosity Extremes-The H i Nearby Galaxy Survey sample. The two-dimensional power spectral indices asymptotically become a constant for each galaxy when a significant part of the line profile is integrated. For narrow channel maps, the power spectra become shallower as the channel width decreases, and this shallowing trend continues to our single channel maps. This implies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 86 publications
(151 reference statements)
5
46
1
Order By: Relevance
“…Indeed, previous work (e.g. Elmegreen et al 2001;Padoan et al 2001;Dutta et al 2009b;Zhang et al 2012) have attributed a break in power spectrum to the scale height (h), marking a transition from large scale 2D turbulence to 3D on scales h (but see Combes et al 2012). However, we find that the breaks in the HI spectra always coincide with the resolution limit of THINGS, making it difficult to make robust claims.…”
Section: Overview Of Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous work (e.g. Elmegreen et al 2001;Padoan et al 2001;Dutta et al 2009b;Zhang et al 2012) have attributed a break in power spectrum to the scale height (h), marking a transition from large scale 2D turbulence to 3D on scales h (but see Combes et al 2012). However, we find that the breaks in the HI spectra always coincide with the resolution limit of THINGS, making it difficult to make robust claims.…”
Section: Overview Of Simulation Resultsmentioning
confidence: 99%
“…Observations of the neutral ISM in nearby galaxies have revealed that the HI component often gives rise to simple power law behaviours (P (k) ∝ k −α ), with α typically in the range 1−3, over several ordered of magnitude in scale (e.g. Bournaud et al 2010;Combes et al 2012;Zhang et al 2012;. This points towards the presence of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of background structures on the order of tens of mas will typically probe the ISM of foreground galaxies on scales of tens of pc. This scale nicely bridges the gap between the few pc that can be studied in the Milky Way galaxy ISM in absorption against background radio sources [9], and the more than 100-pc scales that are probed by high resolution 21-cm emission line maps of nearby galaxies [2,12].…”
Section: Introductionmentioning
confidence: 65%
“…Schmidt-Kennicutt plot for the total amount of gas. The green triangles are the average ΣSFR within ΣHI bins of 400 pc sized regions within a sample of dwarf galaxies presented by Roychowdhury et al (2015), the magenta diamond shows data from the LMC (Staveley-Smith et al 2003), the cyan stars are disc averages of local dwarf galaxies from the LITTLE THINGS Survey (Zhang et al 2012), the grey shaded area represents the region in which the bulk of the spatially resolved data points from local spiral galaxies presented by Bigiel et al (2008) at a resolution of 750 pc lie, and the blue and red squares are the spatially resolved data points of GalA and GalB at the highest resolution, respectively. The solid and dashed lines represent lines of constant atomic gas depletion times, where solid is 1 Gyr and dashed 10 Gyr.…”
Section: Star Formation Rate Predictionmentioning
confidence: 99%